(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Coastal plant communities of the classes Cakiletea maritimae and Ammophiletea along the Russian coast of the Sea of Azov were classified according to the Braun-Blanquet approach. Three new associations Artemisio santonici–Crambetum maritimae, Artemisio santonici–Leymetum racemosi, Galio humifusi–Crambetum maritimae and two subassociations G. h.–C. m. typicum and G. h.–C. m. medicaginetosum falcatae were established. Tables of the relevés of the new syntaxa and synoptic comparative tables are given.